Modeling the climatic suitability of leishmaniasis vector species in Europe. Issue 1 (December 2017) - Koch, Lisa; Kochmann, Judith; Klimpel, Sven; Cunze, Sarah
Abstract Climate change will affect the geographical distribution of many species in the future. Phlebotomine sandflies are vector species for leishmaniasis, a tropical neglected disease. We applied an ensemble forecasting niche modeling approach to project future changes in climatic suitability for ten vector competent sandfly species in Europe. Whereas the main area of sandfly distribution currently lies in the Mediterranean region, models generally projected a northwards expansion of areas with suitable climatic conditions for most species (P .alexandri, P .neglectus, P .papatasi, P .perfiliewi, P .tobbi ) in the future. The range of distribution for only two species (P .ariasi, P .mascittii ) was projected to decline in the future. According to our results, a higher number of vector competent species in Central Europe can generally be expected, assuming no limitations to dispersal. We recommend monitoring for the establishment of vector species, especially in areas with projected climatic suitability for multiple vector species, as a precautious strategy. An increased number of vector species, or a higher abundance of a single species, might result in a higher transmission risk of leishmaniasis, provided that the pathogens follow the projected range shifts.